Diferenças principais entre líderes e gerentes e seus respectivos papéis na organização - Haim, Marie (2003)
Leadership and Management do not mean the same thing. Both are important, yet they do have very different functions. Following this line of investigation, the present dissertation considers the possibility of eventual misunderstandings regarding the use of both terms, whenever applied to describe these two organizations' role players. Nowadays, with the rising pace in business change of directions, the development of proper human resources expertise assumes a crucial task. It becomes vital to pursuit something or someone that could help companies get together new alternatives to meet latest challenges. Identifying and distinguishing key differences between Leaders and Managers, as well as their functions in the business are the general objectives of this study. It is also being presented an assessment of the different assumptions already carry out in this subject matter, bearing in mind the importance of making the proper distinction between Leaders and Managers, both performances equally imperative to today companies.